Ordering time, nationalising the past: temporality, historiography and Brazil’s "formation" - de Oliveira, Maria da Glória; Gontijo, Rebeca; Franzini, Fábio (Historein, 2018)
This article presents an overview of historiography in Brazil from the 1840s to the 1950s and delimits the impasses, tensions and disputes in relation to two concomitant processes: the nationalisation of the past and the institutionalisation of historical research in the country. Our central reasoning is that, over the course of this period, the writing of history demanded multifaceted narrative and interpretative reconfigurations regarding the colonial past in order to portray the nation with its multiple temporalities and contrasts. These were perceived as structural traits of the present and explicative causes of Brazil’s alleged “backwardness” vis-à-vis the ideals of civilisation, contributing to a continuous postponement of future expectations regarding the full attainment of modernity. Not by chance, in the early decades of the twentieth century, the use of the formation concept emerged as a fundamental notion in the analysis and understanding of Brazilian history. Not only did it come as a kind of “response” to the problem of nationality but it also suggested that its construction was unfinished and uncertain in character.